Comments on “The principles of a new method, MNF-3D, for concentration of magnetic particles in three-dimensional space” - Dobosz, Bernadeta; Schroeder, Grzegorz; Kurczewska, Joanna (Measurement : journal of the International Measurement Confederation, 2023)
The note comments on the article (Measurement, 112, 2017) describing a new method for focusing magnetic particles in three-dimensional space (MNF-3D). The present paper shows the application of the method in focusing several magnetic nanoparticles composed of magnetite core and different organic shells. It describes the effect of surface organic units on focusing time of the nanoparticles in the magnetic field. The average focusing time of the selected functionalized magnetic nanoparticles ranged from 3.3 to 8.1 min in a saline-serum mixture. The findings could be crucial for determining the focusing mechanism of nanoparticles for biomedical applications.